Circ_0000140 Alters miR-527/SLC7A11-Mediated Ferroptosis to Influence Oral Squamous Cell Carcinoma Cell Resistance to DDP - Ma Y; Gao J; Guo H (Dove Medical Press, 2023)
Yu Ma, Jinbo Gao, Hongning Guo Department of Stomatology, Tianjin Third Central Hospital, Tianjin, People's Republic of ChinaCorrespondence: Yu Ma, Department of Stomatology, Tianjin Third Central Hospital, No. 83 Jintang Road, Hedong District, Tianjin, 300170, People's Republic of China, Tel +86-13102229881, Email mayu881@tom.comBackground: While there is prior evidence for the ability of circular RNAs (circRNAs) to shape the cisplatin (DDP) resistance of cancers in human patients, there has been relatively little research to date focused on the interplay between circRNAs and DDP resistance in the context of OSCC progression to date. In the present analysis, the functional role that circ_0000140 plays as a mediator of chemoresistance to DDP was thus explored in greater detail.Methods: Both qPCR and Western immunoblotting were employed as appropriate to detect circ_0000140, miR-527, and SLC7A11 levels, while interactions among these factors were detected through RNA immunoprecipitation, RNA pull-down, and dual luciferase report assays. MTT assays were used to assess cellular viability as a means of gauging DDP sensitivity.Results: Both tissue samples from DDP-resistant OSCC patient tumors and OSCC cell lines resistant to DDP exhibited pronounced circ_0000140 upregulation. Knocking down this circRNA significantly increased the DDP sensitivity of both tested DDP-resistant OSCC cell lines and promoted ferroptosis, whereas knocking down miR-527 was sufficient to reverse these effects, which were recapitulated by miR-527 overexpression. Conversely, the effects of overexpressing miR-527 were reversed by the restoration of SLC7A11 expression. Consistently, this circRNA was able to increase DDP IC50 values and to suppress ferroptosis in both tested cell lines through this miR-527/SLC7A11 signaling axis.Conclusion: These results revealed that circ_0000140/miR-527/SLC7A11-mediated ferroptosis may provide novel insights into the development of this cancer type and the emergence of chemoresistance in the future.Keywords: Circ_0000140, DDP resistance, oral squamous cell carcinoma, miR-527, SLC7A11, ferroptosis